Feasibility and reproducibility of liver and pancreatic stiffness in patients with alcohol-related liver disease. Issue 7 (July 2019) - Conti, Clara Benedetta; Weiler, Nina; Casazza, Giovanni; Schrecker, Christopher; Schneider, Maximillian; Mücke, Marcus M.; Queck, Alexander; Herrmann, Eva; Conte, Dario; Colombo, Massimo; Zeuzem, Stefan; Fraquelli, Mirella; et al.
Abstract: Background: To date no studies evaluated liver stiffness and pancreatic stiffness by shear-wave elastography, in alcoholic liver disease setting. Aims: To assess feasibility and reproducibility of Shear-wave elastrography in measuring liver and pancreatic stiffness in alcoholic liver disease and investigate the correlation among liver and pancreatic stiffness and clinical data. Methods: Liver and pancreatic stiffness were measured by elastography (2 examiners) in patients with alcoholic liver disease and in healthy volunteers, for reference values. Effect of clinical data was evaluated on log-transformed pancreatic or liver stiffness, using univariate and multivariate linear regression model. Results: 87 patients and 46 healthy volunteers enrolled. Both the stiffness values were higher in patients than healthy volunteers (p < 0.001). For liver stiffness: no failure measurements found, the Intraclass correlation coefficient (between 2 examiners) was 0.72 and the variables significantly correlated at multivariate analysis were cirrhosis (p < 0.0001) and steatosis (p = .007). For pancreatic stiffness: 2 failures found, with ICC 0.40 and the only variable significantly correlated at multivariate analysis was liver cirrhosis (p = .005). Conclusions: Shear-wave elastography feasibility was good for liver and pancreatic stiffness. Reproducibility was good for liver stiffness, whereas fair for pancreatic one. Both the stiffness correlated with alcoholic liver disease severity. Elastography could be a useful tool to detect and monitor alcohol-related liver and pancreatic damage.